Azide–alkyne cycloaddition-mediated cyclization of phosphonopeptides and their evaluation as PTP1B binders and enrichment tools. Issue 12 (15th June 2015) - Meyer, Christoph; Hoeger, Birgit; Chatterjee, Jayanta; Köhn, Maja
Graphical abstract: Abstract: Protein tyrosine phosphatases (PTPs) are important enzymes in health and disease, and chemical tools are crucial to understand and modulate their biological roles. PTP1B is involved in diabetes, obesity and cancer. One of the main challenges for the design of chemical tools for PTP1B is the homology to TCPTP, making tool selectivity a highly challenging task. Here, we aimed to study if azide–alkyne cycloaddition-mediated cyclization of a peptide inhibitor could increase its selectivity toward PTP1B over TCPTP, and if cyclic and linear peptide binders can be applied as enrichment tools of endogenous PTP1B. While the cyclization of the peptide binders did not improve the selectivity toward PTP1B over TCPTP, it enhanced strongly the efficiency to co-precipitate endogenous PTP1B out of cell lysates. Our results show that fine-tuning the molecular structure of peptidic pull-down baits can greatly enhance their efficiency compared to the parental peptide sequences.